2002
DOI: 10.1034/j.1399-5618.2002.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization and costs among privately insured patients with bipolar I disorder

Abstract: Treatment of bipolar disorder, particularly inpatient care, is costly to patients and health insurers. Further study is needed to find ways to reduce the overall cost of managing these patients without jeopardizing patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 17 publications
(11 reference statements)
3
54
1
2
Order By: Relevance
“…11,17,[30][31][32][33] Although the patients screening positive on the MDQ in this study may encompass both bipolar I and bipolar II patients, it is noteworthy that a previous study found that mean 1-year allcause health care costs were nearly 4 times as high for patients with bipolar I disorder as for a comparison group of age-and sex-matched health plan members without a diagnosis of bipolar disorder ($7,663 vs. $1,962, respectively). 34 Rajagopalan et al (2006) found significantly higher all-cause annual health care service costs in employees with bipolar disorder compared with employees with other mental disorders and estimated the annual all-cause health care costs for employees with bipolar disorder at $9,983, compared with $3,147 for a matched comparison group without bipolar disorder. 33 The poor humanistic outcomes in MDQ-positive patients in this study and the burden of illness associated with bipolar disorder reported in previous studies suggest that accurate and early diagnosis of bipolar disorder may result in improved patient outcomes.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17,[30][31][32][33] Although the patients screening positive on the MDQ in this study may encompass both bipolar I and bipolar II patients, it is noteworthy that a previous study found that mean 1-year allcause health care costs were nearly 4 times as high for patients with bipolar I disorder as for a comparison group of age-and sex-matched health plan members without a diagnosis of bipolar disorder ($7,663 vs. $1,962, respectively). 34 Rajagopalan et al (2006) found significantly higher all-cause annual health care service costs in employees with bipolar disorder compared with employees with other mental disorders and estimated the annual all-cause health care costs for employees with bipolar disorder at $9,983, compared with $3,147 for a matched comparison group without bipolar disorder. 33 The poor humanistic outcomes in MDQ-positive patients in this study and the burden of illness associated with bipolar disorder reported in previous studies suggest that accurate and early diagnosis of bipolar disorder may result in improved patient outcomes.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…33 Major depressive affective disorder recurrent episode severe degree without psychotic behavior 296. 34 Major depressive affective disorder recurrent episode severe degree specified as with psychotic behavior 296. 35 Major SDS item and summary scale scores were reported as the proportion of patients with "marked impairment" (score of 7-10 on a scale of 0-10).…”
Section: Burden Of Disease: Humanistic Outcomesmentioning
confidence: 99%
“…It is predicted that the lifetime prevalence of bipolar disorder ranges from 1% to 8%. [1][2][3][4][5][6][7][8] As research continues into the subtypes of bipolar disorder, many experts believe that bipolar disorder may be as widespread as unipolar depression, though not as widely recognized.…”
mentioning
confidence: 99%
“…Recovery from episodes normally takes months and in total patients suffers from various types of affective symptoms about 50% of the time even if they are appropriately treated receiving mood stabilizing medication [5]. The burden of total health care for patients with BD is estimated at two to four times higher than for age and sex matched controls [6].…”
Section: Introductionmentioning
confidence: 99%